2022
DOI: 10.2147/ijgm.s343152
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Molecular Subtypes and Related Prognostic and Immune Response Models Based on M2 Macrophages in Glioblastoma

Abstract: Objectives To identify the molecular subtypes of glioblastoma multiforme (GBM) related to M2 macrophage-based prognostic genes, then to preliminarily explore their biological functions and construct immunotherapy response gene models. Material and Methods We used R language to analyze GBM microarray data, and other tools, including xCell and CIBERSORTx, to identify subtypes of GBM that related to M2 macrophages. The process started with the exploration of biological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…GBM is the most common type of grade IV gliomas 46 . Although many tumor treatment have been improved in the past few decades, few effective drugs have been approved by FDA for GBM therapy because of the blood–brain barrier 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBM is the most common type of grade IV gliomas 46 . Although many tumor treatment have been improved in the past few decades, few effective drugs have been approved by FDA for GBM therapy because of the blood–brain barrier 47 .…”
Section: Discussionmentioning
confidence: 99%
“…GBM is the most common type of grade IV gliomas. 46 Although many tumor treatment have been improved in the past few decades, few effective drugs have been approved by FDA for GBM therapy because of the blood–brain barrier. 47 Recent studies revealed that immune checkpoint inhibitors appear to be an effective anticancer strategy in glioma immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells with significant differences between the disease group and the control group were found for the subsequent analysis with p.adjust <0.05. Then, the CIBERSORT algorithm [ 22 , 23 ] was further used to verify the difference in the proportion of M2 macrophages between two groups.…”
Section: Methodsmentioning
confidence: 99%